Microorganisms in coffee fermentation: A bibliometric and systematic literature network analysis related to agriculture and beverage quality (1965-2019) - Cruz-O’Byrne, Rosmery; Piraneque-Gambasica, Nelson; Aguirre-Forero, Sonia; Ramirez-Vergara, Jose (Coffee Science - ISSN 1984-3909, 2020)
The activity of microorganisms in coffee fermentation has a great influence on the composition of the beans and their beverage quality. In the present study a bibliometric and systematic literature network analysis is made to examine the growth in the literature and the flow of knowledge in the field of study. The bibliometric information was retrieved from the Scopus database, obtaining 55 articles between 1965 and 2019. Frequencies, co-authorship, and co-occurrence The activity of microorganisms in coffee fermentation has a great influence on the composition of the beans and their beverage quality. In the present study, a bibliometric and systematic literature network analysis is made to examine the growth in the literature and the flow of knowledge in the field of study. The bibliometric information was retrieved from the Scopus database, obtaining 55 articles between 1965 and 2019. Frequencies, co-authorship, and co-occurrence indicators were analyzed using Microsoft Excel and VOSviewer software. Our findings show that most of the articles have been published in the last decade and mainly on microbial diversity and starter cultures. Furthermore, it was possible to identify the most productive authors, the most influential works, the main journals where articles of the most productive authors and the most influential works have been published, the most productive affiliation countries, the most used keywords, the co-authorship taking authors and countries as the unit of analysis, the keyword co-occurrence, and the spatial distribution of studies with their research topics. This is the first bibliometric and systematic literature network analysis carried out on research articles on microorganisms in coffee fermentation related to agriculture and beverage quality, which becomes a tool for researchers in making decisions for the building and development of strategic plans for future research by understanding the trends and status of existing research in the field of study in accordance with the authors, works, affiliation countries, study topics, and patterns of international collaboration and within the academic community. Key words: Bibliometry; Coffea; coffee processing; cup quality; microbiology.